2022
DOI: 10.1155/2022/6297484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Neuropathic Pain Induced by Spinal Cord Injury: A Systematic Review and Meta-Analysis

Abstract: Introduction. Neuropathic pain is a commonly seen symptom and one of the most intractable comorbidities following spinal cord injury (SCI). Acupuncture has been widely used for neuropathic pain after SCI in clinical settings. There is no systematic review or meta‐analysis evaluating the efficacy of acupuncture in the treatment of SCI-induced neuropathic pain. Thus, this study aimed to conduct a systematic review and meta-analysis to assess the efficacy of acupuncture on SCI-induced neuropathic pain. Methods. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Acupuncture is an effective therapeutic method, which has been widely practiced in China for more than 2,000 years. Several systematic reviews and meta-analyses have demonstrated that acupuncture can improve symptoms of CNS disorders, and its anti-inflammatory effects have long been proven (Chen et al, 2022b, He et al, 2022Lin C. J. et al, 2022;Zhou Z. et al, 2022). Exhilaratingly, PROKR2 neurons are indispensable for the anti-inflammatory effect of low-intensity electroacupuncture (EA) through the vagal-adrenal axis, which was once again confirmed by the article published in the authoritative journal NATURE last year (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Acupuncture is an effective therapeutic method, which has been widely practiced in China for more than 2,000 years. Several systematic reviews and meta-analyses have demonstrated that acupuncture can improve symptoms of CNS disorders, and its anti-inflammatory effects have long been proven (Chen et al, 2022b, He et al, 2022Lin C. J. et al, 2022;Zhou Z. et al, 2022). Exhilaratingly, PROKR2 neurons are indispensable for the anti-inflammatory effect of low-intensity electroacupuncture (EA) through the vagal-adrenal axis, which was once again confirmed by the article published in the authoritative journal NATURE last year (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Electroacupuncture (EA) is a combination of traditional acupuncture and electric current therapy, as an alternative and complementary strategy, has been widely used in the treatment of SCI with multi‐target therapy in clinical practice 24,25 . Many researchers have proved that EA can not only relieve neuropathological pain after SCI, 26 promote the repair of motor function of injury, 27 but also improve intestinal peristalsis 28 and bladder dysfunction 29 caused by injury. It plays a particular role in the process of neuronal repair post‐SCI 30–32 .…”
Section: Introductionmentioning
confidence: 99%